2015
DOI: 10.1097/ccm.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Is Long-Axis View Superior to Short-Axis View in Ultrasound-Guided Central Venous Catheterization?*

Abstract: Objective To evaluate whether using long axis (LA) or short axis (SA) view during ultrasound-guided internal jugular (IJ) and subclavian (SC) central venous catheterization (CVC) results in fewer skin breaks, decreased time to cannulation, and fewer posterior wall penetrations (PWP). Design Prospective, randomized crossover study. Setting Urban emergency department with approximate annual census of 60,000. Subjects Emergency medicine resident physicians at the Denver Health Residency in Emergency Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 25 publications
(18 reference statements)
1
55
2
5
Order By: Relevance
“…15 16 Experimental evidence shows that PVWP occurs more frequently with SAX. 17 A few clinical studies have evaluated LAX, and the results of these studies are comparable with those of our own study regarding LAX. 12 13 Studies comparing transducer orientation approaches for ultrasound-guided IJVC in the clinical setting are scarce.…”
Section: Discussionsupporting
confidence: 75%
“…15 16 Experimental evidence shows that PVWP occurs more frequently with SAX. 17 A few clinical studies have evaluated LAX, and the results of these studies are comparable with those of our own study regarding LAX. 12 13 Studies comparing transducer orientation approaches for ultrasound-guided IJVC in the clinical setting are scarce.…”
Section: Discussionsupporting
confidence: 75%
“…The best ultrasound approach is still under debate. [21][22][23][24] The success rate recorded in our study is slightly lower than that of other published series. [6][7][8][9] Yet, it is worth noting that a 90% success rate was achieved with a third attempt and that, in about 20% of the cases, it was possible to puncture the vessel but not to cannulate it.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, operators reported that hand‐eye coordination was improved by in‐line projection of US images onto the procedural site. Using an in‐plane needle approach with a long‐axis view of the vessel is superior to the short‐axis view for visualizing the entire subcutaneous portion of the needle, thus avoiding inadvertent puncture of distal structures . However, it is difficult to keep the needle in the same plane as the narrow US beam in the long‐axis view during the procedure .…”
Section: Discussionmentioning
confidence: 99%